2022
DOI: 10.3346/jkms.2022.37.e11
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Hearing Aid Adoption in Patients With Hearing Loss in Korea

Abstract: Background The purpose of this study was two-fold: 1) to identify differences in the characteristics of adopters and non-adopters of hearing aids (HAs); and 2) to investigate factors influencing the purchase of HA. Methods This study was conducted among 1,464 subjects (818 male and 646 female) with hearing loss. A national face-to-face survey was performed from August 2019 to October 2020 by otologists or HA experts. The questionnaire consisted of three domains: demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…Four studies reported that people were more likely to take up hearing aids if they had higher socioeconomic status or household income ( Cho et al, 2022 ; Laplante-Lévesque et al, 2012 ; Simpson et al, 2019 ; Tahden et al, 2018 ), although three studies did not report any association. A study by Meyer et al (2014) reported that older adults were more likely to obtain hearing aids if they received a pension.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four studies reported that people were more likely to take up hearing aids if they had higher socioeconomic status or household income ( Cho et al, 2022 ; Laplante-Lévesque et al, 2012 ; Simpson et al, 2019 ; Tahden et al, 2018 ), although three studies did not report any association. A study by Meyer et al (2014) reported that older adults were more likely to obtain hearing aids if they received a pension.…”
Section: Resultsmentioning
confidence: 99%
“… Chan et al (2017) reported that the age of hearing loss onset was correlated with time to hearing aid acquisition, with older people acquiring hearing aids more quickly than younger people, and Moschis et al (2015) concluded that the older the person at the time of diagnosis, the more likely they were to purchase a hearing aid. Three studies reported that people were more likely to take up hearing aids if they had a longer hearing loss duration ( Cho et al, 2022 ; Moschis et al, 2015 ; Saunders et al, 2016 ), although two studies reported no association.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For a long time, there have been many studies to find out the factors which are good enough to consistently differentiate successful from unsuccessful hearing aid candidates [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Unfortunately, no factor has been found yet, although certain parameters were statistically significantly related to individual measures of successful hearing aid use [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. “Two hearing aids work better than one” has been one of the conventional principles in hearing rehabilitation, even though there may be some exceptions [ 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%